Gaining from vertical partnerships: knowledge transfer, relationship duration, and supplier performance improvement in the U.S. and Japanese automotive industries - Kotabe, Masaaki; Martin, Xavier; Domoto, Hiroshi (Strategic management journal, 2003)
We study sources of operational performance improvement in supplier partnerships. We argue that supplier performance will benefit most where time-bound relational assets have developed between a buyer and supplier and the firms exploit the resulting communication efficiency by transferring productive knowledge. We examine the effects of two forms of knowledge exchange together with the prior duration of the buyer--supplier relationship. We find similar interaction patterns in two survey samples of Japanese and U.S. automotive suppliers. The effect of ordinary technical exchanges on supplier performance improvement does not vary with relationship duration. The effect of higher-level technology transfer, however, grows more positive as relationship duration increases. Other results show relevant contrasts consistent with heterogeneous sourcing behavior between the two countries. The findings highlight the role of relational assets and show that it is important to distinguish between simple techniques and higher-level technological capabilities when studying interfirm relationships. This research extends the literatures on knowledge transfer, buyer--supplier partnerships, and the performance dynamics of interfirm and intrafirm relationships in general.